Acute Post-infectious Glomerulonephritis in Children Admitted to a Tertiary Care Hospital: A Descriptive Cross-sectional Study - Mandira Shrestha; Romila Chimoriya; Amrit Dhungel; Sujit Koirala; Rohit Bhatta; Bijay Basnet (Journal of Nepal Medical Association, 2024)
Introduction: Post infectious glomerulonephritis remains the most common cause leading to the majority of hospital admissions in children of developing countries like ours. The aim of our study was to find the prevalence of post infectious glomerulonephritis, study the clinical profile, biochemical changes and its complication in children admitted in a tertiary care hospital of Nepal.